2013
DOI: 10.1108/ijpdlm-11-2011-0200
|View full text |Cite
|
Sign up to set email alerts
|

Creating sustainable fresh food supply chains through waste reduction

Abstract: Purpose-The aim of this empirical paper is to study information sharing in fresh food supply chains, with a specific goal of reducing waste and facilitating sustainable performance. The study focuses on material and information flow issues, specifically on sharing demand and shelf-life data. Design/methodology/approach-This work has been designed as an exploratory case study in three fresh food supply chains, milk, fresh fish, and fresh poultry, in the Nordic countries. The cases are based on interviews and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 25 publications
(41 reference statements)
4
181
0
2
Order By: Relevance
“…A further programme was set up to foster information exchange between retailers and suppliers with the aim of providing more accurate and timely demand forecasting [16]. The effect of such vertical information exchange was also evaluated by Kaipia et al [17] in three case studies in Nordic countries. They showed that losses at retailers could be largely reduced by an automated demand forecast based on a better information flow.…”
Section: The Challenge To Avoid Losses In the Food Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…A further programme was set up to foster information exchange between retailers and suppliers with the aim of providing more accurate and timely demand forecasting [16]. The effect of such vertical information exchange was also evaluated by Kaipia et al [17] in three case studies in Nordic countries. They showed that losses at retailers could be largely reduced by an automated demand forecast based on a better information flow.…”
Section: The Challenge To Avoid Losses In the Food Chainmentioning
confidence: 99%
“…Beside the work on demand forecasting [16,17] mentioned in §2, Scheer [26] focused on the integration of such aspects with quality tracing and FEFO planning. He suggested a selflearning demand and supply chain management system at the retailer level that gives advice on recommended order quantities, based on reported daily sales and waste owing to overstock.…”
Section: (I) Selection Of Logistic Service Providersmentioning
confidence: 99%
“…Fruits and vegetables are delicate products that are subjected to a number of natural and physical sources of deterioration during the marketing process that leads to food loss [4][5][6][7][8][9][10]. The high loss levels reported (typically~35%) are serious threats to food security and the long-term economic sustainability of the food supply chain for present and future generations [1,[11][12][13]. In addition, fruit and vegetable shortages resulting from loss can also contribute to commodity price increases [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in mind the magnitude of food losses, building beneficial interests in decreasing losses could be one method for lessening the expense of food (Food and Agriculture Organization of United Nations, 2014). Food waste is a serious problem in environmental, social & economic terms (Kaipia, et al, 2013) (Gustavsson, et al, 2011). The economic losses have been calculated to cost in to the billions (Food and Agriculture Organization of United Nations, 2015) (Jones, 2004).…”
Section: Economic Impact Of Food Wastagementioning
confidence: 99%